Lessons Learnt during the COVID-19 Pandemic: For Patients with End-Stage Renal Disease, We Should Prioritize Home-Based Treatment and Telemedicine - Brunori, Giuliano (Kidney Blood Press Res, 2021)
BACKGROUNDS: The recent coronavirus disease 2019 (COVID-19) pandemic has placed worldwide health systems and hospitals under pressure, and so are the renal care models. This may be a unique opportunity to promote and expand alternative models of health-care delivery in patients undergoing renal replacement therapies. SUMMARY: Despite the high risk of acquiring communicable diseases when undergoing in-centre treatments, only a small proportion of patients are currently being treated with home therapies. Recent data provided by the Italian Society of Nephrology (SIN), the REIN French Registry and the Wuhan Hemodialysis Quality Control Center clearly show that patients receiving hospital-based treatment have a 3- to 4-fold greater risk of infection, and a subsequent fatality proportion between 21 and 34%. On the other hand, home-based therapy can be managed remotely, there is little or no need for transport to and from the hospital, and it is less expensive. Besides, the digital revolution in health care with the development of virtual care systems can make home dialysis with telehealth a cost-effective solution for both patients and health-care providers. Such a transition would require specific training for physicians and health-care professionals and a functional re-organization of dialysis centres to improve the skills and expertise in caring for patients at home. CONCLUSION: The need for more widespread home treatment is the main lesson learnt by nephrologists by the COVID-19 pandemic.